Integrasi Nilai Ihsan dalam Supervisi Akademik untuk Meningkatkan Profesionalisme Guru - Melja Safitri; Agustin Agustin; Muhammad Iqbal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Academic supervision is among the key instruments for improving the quality of learning and teacher professionalism. However, the implementation of supervision in the field often still contains administrative elements and lacks attention to the moral-spiritual aspects that are the main foundation of Islamic education. This study aims to analyze the application of the principle of ihsan in academic supervision thru a qualitative literature review. The principle of ihsan, which encompasses spiritual awareness, the highest quality, and sincerity in work, is considered relevant for improving the quality of interaction between supervisors and teachers. The analysis results show that the value of ihsan can be integrated into three stages of supervision: planning, observation, and feedback. In the planning stage, ihsan encourages the formulation of humanistic and improvement-oriented supervision goals, not just evaluation. In the observation stage, ihsan manifests in the form of honesty, empathy, and appreciation for teachers' efforts. Meanwhile, in the feedback stage, the value of ihsan strengthens the pattern of dialogical, gentle (rifq), and motivating communication to help teachers develop optimally. This study emphasizes that integrating the principles of ihsan can shape academic supervision that is more meaningful, humanistic, and aligned with the values of contemporary Islamic education.